2000
DOI: 10.1097/00005392-200011000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic Carcinoma: A Nutritional Disease? Conflicting Data From the Kingdom of Saudi Arabia

Abstract: The incidence of prostatic carcinoma in the Kingdom of Saudi Arabia is low despite a high saturated fat diet in recent years. This finding contradicts most western clinical studies, which indicate a positive association of a high fat diet with prostatic carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 13 publications
0
12
0
3
Order By: Relevance
“…Screening for prostate cancer is in its infancy in Kuwait, as in other Arab countries, because of the very low incidence of the disease in this region [6–8]. Thus, of the 1700 PSA estimations, only 9.2% were requested for patients with no prostatic symptoms, but as screening for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening for prostate cancer is in its infancy in Kuwait, as in other Arab countries, because of the very low incidence of the disease in this region [6–8]. Thus, of the 1700 PSA estimations, only 9.2% were requested for patients with no prostatic symptoms, but as screening for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the Middle East, the incidence of prostate cancer is relatively low [6–8], but the disease is being increasingly encountered by urologists in the region. The present study investigated Arab men with a serum tPSA of> 10 ng/mL, to determine the proportion who had underlying prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This was a large cohort (20,316) of multiethnic men living in Hawaii with 9 to 14 yr of follow-up and 198 cases of prostate cancer (216). Exactly why prospective cohort studies have not confirmed the international data showing a strong relationship between fat consumption and prostate cancer is unclear but might relate to evidence that other dietary components such as fruits, vegetables, fiber, and cereals may have beneficial effects, independent of fat intake (132) and/or due to lack of variability in dietary fat consumption. Another possibility is a variation in the type of fat consumed.…”
Section: Cancermentioning
confidence: 99%
“…In Saudi Arabia, the incidence of PCa was documented at 3AE1 ⁄ 100 000 personyears in the year 2000 [1]. Although considered low, the recent rise in the prevalence of obesity and metabolic syndrome in the kingdom [2,3], which are considered modifiable risk factors for PCa aggressiveness, as well as the ageing of the population, may lead to increased incidence for this type of malignancy in the years to come.…”
Section: Introductionmentioning
confidence: 99%